Psychological effects of orphans affected and infected by HIV/AIDS : a study done in Meyerton, South Gauteng - Stimela, Julia Zanele (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.